2014
DOI: 10.1038/srep06592
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in oral fluids of HIV-1-positive men:prevalence and risk factors

Abstract: Human papillomavirus is one of the most common sexually transmitted diseases worldwide. The natural history of oral HPV infection is unclear, and its risk factors have not been explored. Immunocompromised individuals, as exemplified by HIV patients, are at high risk for HPV-related diseases. The mean of this study is to determine the prevalence ofHPV in the oral tract of HIV-1-positive male subjects and its association with risk factors. A total of 283 oral wash samples from HIV-1-positive men were tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
6
22
0
1
Order By: Relevance
“…Our findings also support the previously reported association between oral HPV and HIV‐positive smokers . Some authors have observed odd ratios (from 2.8 5 to 10 14 ) for HPV infection in HIV smokers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings also support the previously reported association between oral HPV and HIV‐positive smokers . Some authors have observed odd ratios (from 2.8 5 to 10 14 ) for HPV infection in HIV smokers.…”
Section: Discussionsupporting
confidence: 93%
“…Among individuals with HIV, varying percentages of HR‐HPV sequences, from 3.5% to 24.8%, have been reported, the latter of which is similar to the 26.8% observed in this prospective study. Interestingly, the cohort studied by Mooij et al shares some characteristics with that of our study, such as MSM being the predominant transmission category.…”
Section: Discussionsupporting
confidence: 85%
“…HPV‐16 was the most prevalent high‐risk HPV in both study groups (together with HPV‐18 in HIV‐infected subjects). HPV‐16 has been described as the most common high‐risk type in oral infections in other studies conducted on similar populations, although other high‐risk HPVs emerged as more frequent in other investigations …”
Section: Discussionmentioning
confidence: 99%
“…Going into the study we expected that the HIV-positive cohort might be much more susceptible to HPV-induced head and neck cancers and the proportion of HPV-positive tumors would be much higher in the HIV-infected group. This was based on studies demonstrating the higher prevalence and persistence of oral HPV infection in HIV-positive groups compared with a healthy population (12, 13). Furthermore, it was expected that the HIV infected individuals with head and neck cancer would have poorer outcome due to immunosuppression from their underlying HIV infection and associated health risks, including higher rates of smoking, intravenous drug use, complications of AIDS and susceptibility to other infections and inflammation(2, 1416).…”
Section: Discussionmentioning
confidence: 99%